2001
DOI: 10.1002/etc.5620200817
|View full text |Cite
|
Sign up to set email alerts
|

Influences of aquatic plants on the fate of the pyrethroid insecticide Lambida‐cyhalothrin in aquatic environments

Abstract: Aquatic exposure assessments for pesticides are generally based on laboratory studies performed in water alone or water sediment systems. Although aquatic macrophytes, which include a variety of bryophytes, macroalgae, and angiosperms, can be a significant component of many aquatic ecosystems, their impact on pesticide fate is generally not included in exposure assessments. To investigate the influence of aquatic plants on the fate and behavior of the pyrethroid insecticide lambda (lambda)-cyhalothrin, two lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Prevention of oxidative damage to cells has been suggested as one of the mechanisms of stress tolerance (Parween et al, 2012a,b). During pesticide exposure, the uptake, metabolization and accumulation of these compounds can occur in aquatic macrophytes (Karen et al, 1998;Knuteson et al, 2002;Gao et al, 2000;Hand et al, 2001;Pietsch et al, 2006). Differences in plant metabolism are considered the major cause of variation in pesticides sensitivity among species.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of oxidative damage to cells has been suggested as one of the mechanisms of stress tolerance (Parween et al, 2012a,b). During pesticide exposure, the uptake, metabolization and accumulation of these compounds can occur in aquatic macrophytes (Karen et al, 1998;Knuteson et al, 2002;Gao et al, 2000;Hand et al, 2001;Pietsch et al, 2006). Differences in plant metabolism are considered the major cause of variation in pesticides sensitivity among species.…”
Section: Introductionmentioning
confidence: 99%
“…The latter process seems more likely, particularly with respect to the short time periods involved. However, the role of plants including attached algal and microbial communities for insecticide sorption has already been demonstrated by various other workers (2,4,25,30,31).…”
Section: Resultsmentioning
confidence: 89%
“…The average removal percentage of pyrethroids by the NaCl solution is lower than that of tap water, except at the 0.1% concentration, whereas removal of pyrethroids by NaHCO 3 was more effective than tap water at high concentrations, especially for fenpropathrin. This may be due to the alkaline nature of the solution (pyrethroid pesticides are stable in acidic and neutral conditions but aqueous hydrolysis occurs under alkaline conditions) can enhance the solubility, and the release from the A. polytricha [ 29 ]. A similar process was studied by Wang et al [ 30 ] who found that soaking in a dilute alkaline solution (pH 9.0) only eliminated 37.82% of the residues of the β-cypermethrin in contaminated vegetables, further demonstrating that pesticides have different behavior in different materials.…”
Section: Resultsmentioning
confidence: 99%